Effects of different pre-treatment methods on anaerobic mixed microflora for hydrogen production and COD reduction from domestic effluent. (August 2019) - Primasari, B; Tamin, M Z A; Mustafa, M A H
Abstract: Effects of different pretreatment methods on sludge inoculum were evaluated concerning hydrogen (H2 ) production enhancement and COD (chemical oxygen demand) reduction, using domestic effluent in a batch system. The sludge was taken from a recycled line of the activated sludge reactor. Two types of pretreatment were investigated, heat treatment and chloroform treatment. The experiment was conducted at pH 4-6 and inoculum sizes of microbes were 10%, 20%, and 30% respectively; and experiment without sludge pretreatment was also conducted as control. The result showed that 30% COD reduction was achieved for chloroform pretreatment at pH 3 and 10% inoculum size. For heat treatment, a maximum COD removal of 60% was achieved in the experiment at pH 6 and 10% inoculum size. In chloroform pretreatment, a maximum volume of gas evolved was 3.6 mL, at pH 3 and 20% inoculum size. For heat pretreatment, maximum biogas evolved was 2.1 mL, at pH 3 and 10% inoculum size. The experimental results showed that the pretreatment methods (heat treatment and chloroform treatment) at 35 °C and initial pH 5.5 had a positive influence on H2 production yield and COD removal efficiency during the fermentative H2 production as compared to the control experiments (without pretreatment). Heat treatment method was shown to be a simple and useful method for enhancing both H2 producing and COD removal processes from domestic effluent with highest H2 yield and COD removal efficiency at 0.314 mmol H2 /g COD and 86%, respectively.